Aggression in High School. A Descriptive Study of Perception in teenagers of 9 urban-popular schools of the Metropolitan Region - Ramos Pavez, Carla; Redondo Rojo, Jesús Ma. (Revista de Psicología, 2004)
Since the decade of the eighties, the subject of violence and aggression has begun to acquire importance associated to the development of the themes of youth and poverty. One of the axes of analysis for this phenomena has been located in the School, as a space of formal instruction, but also as an agent of construction and reproduction of the society and its coexistence. The present study showed contribute to the understanding of the aggressive phenomena taking place in urban-popular high school contexts from the student’s perception of nine high schools of the Metropolitan Region. The main findings showed that the aggressions exhibited in these schools are not exclusive of the youth condition, but due to a complex, relational context which is mediated by the characteristics of the organization and the school culture. In fact, it is possible to give an account of the school context which favors the development and reproduction of these aggressive expressions. Finally, to approach this problem in the educational context, the actors are invited to participate in the macro-structural level as well as the local level, to consider the urgent need to respond to the development and consolidation of a school and social armonic coexistence, based on the construction of a process of sociocultural integration, in which diversity and the exercise of power are respected, aspects which represent the nucleus of psycho-social development.